Biofuels-related materials deterioration in biorefineries, transportation and internal combustion engines: a technical review. (17th February 2022) - Hosseinabadi, Navid; Moheimani, Navid R.; Javaherdashti, Reza
ABSTRACT : Biofuels, like any high-affinity chemical mixtures; can cause tribological effects at interfaces with metallics (ferrous-nonferrous) and non-metallics due to medium assisted activation of corrosion by unsaturated components. The damages; corrosion and tribological effects on surfaces (abrasive wears and edge/cosmetic corrosion), also include contamination and biofuels replacement due to quality decrease. The most common phenomena include the oxidation of biodiesel which increases its affinity towards metallic counterparts, i.e. automotive parts or processing apparatus, via formation of peroxide compounds by oleic acid, linoleic acid, and linolenic acids. This corrosion receptive medium causes pitting; due to high water content and high electronegativity of dissolved oxygen, and galvanic corrosion; due to high electrical conductivity. The main factors for higher aggressive corrosivity of biofuels can be summarized as high electrical conductivity, polarity, solubility, and hygroscopicity. This paper closely reviews the materials deterioration in contact with biofuels and possible corrosions.